1960
DOI: 10.1177/00220345600390020201
|View full text |Cite
|
Sign up to set email alerts
|

The Localization of Microörganisms in Inflamed Dental Pulps of Rats Following Bacteremia

Abstract: It has been recognized for some time that the dental pulp may be invaded by microorganisms either through pulpal exposures or by a vascular route. Robinson and Boling' studied the localization of streptococci and staphylococci in pulps of adult cats, some with naturally acquired infections and others with artificially induced bacteremias. In these over-all findings, pulps of 72 per cent of operated teeth and 8.5 per cent of control teeth contained bacteria when the animals were sacrificed. Robinson and Boling1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1972
1972
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Pulpal infection can also occur through exposed dentinal tubules at the cervical root surface, due to gaps in the cemental coating. Microbes have also been claimed to 'seed' in the necrotic pulp via the blood circulation (anachoresis) (Robinson and Boling, 1941;Burke and Knighton, 1960;Gier and Mitchel, 1968;Allard et al, 1979). However, bacteria could not be recovered from the root canals when the blood stream was experimentally infected, unless the root canals were over-instrumented and presumably the apical periodontal blood vessels were injured during the period of bacteremia (Delivanis and Fan, 1984).…”
Section: (B) Portals Of Root Canal Infectionmentioning
confidence: 99%
“…Pulpal infection can also occur through exposed dentinal tubules at the cervical root surface, due to gaps in the cemental coating. Microbes have also been claimed to 'seed' in the necrotic pulp via the blood circulation (anachoresis) (Robinson and Boling, 1941;Burke and Knighton, 1960;Gier and Mitchel, 1968;Allard et al, 1979). However, bacteria could not be recovered from the root canals when the blood stream was experimentally infected, unless the root canals were over-instrumented and presumably the apical periodontal blood vessels were injured during the period of bacteremia (Delivanis and Fan, 1984).…”
Section: (B) Portals Of Root Canal Infectionmentioning
confidence: 99%
“…Blood-borne bacteria because of generalized bacteremia have also been suggested to be the source of pulpal infection (97,(102)(103)(104)(105). However, Delivanis & Fan (106) were not able to demonstrate bacteria in instrumented unfilled root canals of dogs despite repeated injection of bacteria into the bloodstream.…”
Section: Psmentioning
confidence: 99%
“…In intrusion of the teeth, plaque accumulation situated in the cervical part of the crown may also bring bacteria into the wound site (1). Another possibility is invasion by the existing blood supply (anachoresis) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). It has been shown that periodic bacteremia occurs in all individuals, usually with the bacterial origin from the marginal periodontium (27).…”
Section: Bacterial Contamination In Traumatic Dental Injuriesmentioning
confidence: 99%